MODEL PERENCANAAN KARIR PRANATA KOMPUTER - Tiara Rachmalia (JURNAL TEKNIK INDUSTRI, 2015)
Functional position has disadvantage that for promotion of PNS not certainly, depands onPNS can reach specified requirements. Pranata Komputer as one of functional positions alsohas same disadvantage. Because of that, it needs career planning model for PrantaKomputer so that time for promotion is decent. Career planning model designed based onthree stages of a career, which is entry stage, maturity stage, and passage stage. Careerplanning model designed influenced by elements of activities, events, and credit numbers.The verification results show that the model has been as expected. The validation result showthat activities designed for promotion have a high suitability, but for ease of implementationdiffers in each rank.